1983
DOI: 10.1093/jn/113.8.1643
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Fish on the Bioavailability of Plant Iron in the Anemic Rat

Abstract: The effect of fish protein and fish oil on the utilization of endogenous iron in wheat bran, spinach and soy protein isolate was investigated by using the anemic rat as an animal model. Marine products were substituted for casein and corn oil in the diets of these animals. Hemoglobin regeneration was one criteria used to measure iron uptake. Relative biological values (RBV) were computed from a regression equation obtained from control animals receiving graded levels of FeSO4 X 7H2O. The RBV of iron from plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 99 publications
1
9
0
Order By: Relevance
“…Water-soluble oxalic acid in spinach, included in a small quantity (3), might have no interference with calcium absorption. From the present study's results about rats' calcium absorption from spinach, it was thought that the absorption of calcium in spinach by rats was equal (11,13) to or lower (12,14,40) than the iron absorption rate from spinach as reported by other investigators. In the present study, calcium absorption from raw powdered spinach and boiled-powdered spinach by calcium-deficient rats was about 36 and 27%, respectively.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Water-soluble oxalic acid in spinach, included in a small quantity (3), might have no interference with calcium absorption. From the present study's results about rats' calcium absorption from spinach, it was thought that the absorption of calcium in spinach by rats was equal (11,13) to or lower (12,14,40) than the iron absorption rate from spinach as reported by other investigators. In the present study, calcium absorption from raw powdered spinach and boiled-powdered spinach by calcium-deficient rats was about 36 and 27%, respectively.…”
Section: Discussionsupporting
confidence: 60%
“…However, there are different reports that show spinach in the diet depressed calcium absorption (5-7), and did not adversely affect calcium balance (8)(9)(10). Also, bioavailability of iron in spinach was lower than that in cereal (11)(12)(13). But Gordon and Chao reported that dietary oxalic acid and phytic acid increased the relative biological value of iron (FeSO4=100%) (14).…”
mentioning
confidence: 97%
“…Faustman et al (1992) observed that the initial MetMb formation was significantly correlated with the total iron or nonheme iron. As above mentioned, lower iron absorption with increasing the degree of unsaturation of the fatty acids in diet has been reported (Chao & Gordon, 1983). Again, the higher long-chain n-3 PUFA content in FO diet could explain the lower MetMb proportion in FO meat.…”
Section: Values Of Ph Colour Parameters and Pigment Proportionsmentioning
confidence: 71%
“…The fatty acid profile of the experimental diet could also have affected the meat pigment content and the iron absorption. In this respect, Chao & Gordon (1983) concluded that a diet high in fish oil fatty acid administered as a unique source of fat, can cause metabolic alterations, including iron depletion. Droke et al (2003) observed, in a study in Caco-2 cell line, that iron uptake was dependent on the degree of saturation of the fatty acids, the higher the unsaturation the lower the iron uptake.…”
Section: Values Of Ph Colour Parameters and Pigment Proportionsmentioning
confidence: 99%
“…These authors concluded that the consumption of fresh sardine as the only dietary fat source provoked iron depletion. Chao and Gordon [25] reported that the iron absorption decreased significantly when rats were fed wheat bran, spinach and soy protein with fish oil and increased when they were fed by these foods with fish protein. Some studies have demonstrated that animal fats are able to reduce the iron bioavailability when added to vegetable diets [25].…”
Section: Discussionmentioning
confidence: 99%